Safety and efficacy of renal sympathetic denervation: a 9-year long-term follow-up of 24-hour ambulatory blood pressure measurements - Vogt, Alexander; Dutzmann, Jochen; Nußbaum, Michael; Hoyer, Daniel; Tongers, Jörn; Schlitt, Axel; Sedding, Daniel; Plehn, Alexander (Frontiers in Cardiovascular Medicine, 2023)
Background Renal sympathetic denervation (RDN) has been shown to lower arterial blood pressure both in the presence and in the absence of antihypertensive medication in an observation period of up to 3 years. However, long-term results beyond 3 years are scarcely reported. Methods We performed a long-term follow-up on patients who were previously enrolled in a local renal denervation registry and who underwent radiofrequency RDN with the Symplicity Flex® renal denervation system between 2011 and 2014. The patients were assessed to evaluate their renal function by performing 24-hour ambulatory blood pressure measurement (ABPM), recording their medical history, and conducting laboratory tests. Results Ambulatory blood pressure readings for 24 h were available for 72 patients at long-term follow-up (FU) [9.3 years (IQR: 8.5–10.1)]. We found a significant reduction of ABP from 150.1/86.1 ± 16.9/12.0 mmHg at baseline to 138.3/77.1 ± 16.5/11.1 mmHg at long-term FU (P < 0.001 for both systolic and diastolic ABP). The number of antihypertensive medications used by the patients significantly decreased from 5.4 ± 1.5 at baseline to 4.8 ± 1.6 at long-term FU (P < 0.01). Renal function showed a significant but expected age-associated decrease in the eGFR from 87.8 (IQR: 81.0–100.0) to 72.5 (IQR: 55.8–86.8) ml/min/1.73 m2 (P < 0.01) in patients with an initial eGFR > 60 ml/min/1.73 m2, while a non-significant decrease was observed in patients with an initial eGFR < 60 ml/min/1.73 m2 at long-term FU [56.0 (IQR: 40.9–58.4) vs. 39.0 (IQR: 13.5–56.3) ml/min/1.73 m2]. Conclusions RDN was accompanied by a long-lasting reduction in blood pressure with a concomitant reduction in antihypertensive medication. No negative effects could be detected, especially with regard to renal function.